Integration of Multiple Intelligence Theory in Curriculum Implementation for Developing Student Potential in Indonesia - Setyawan, Jefri; Lumbantoruan, Jitu Halomoan; Listiani, Hanida; Judijanto, Loso (Universitas Pendidikan Indonesia, 2024)
Education in Indonesia is experiencing a transformation through the integration of multiple intelligence theories in the curriculum to optimize student potential. The problem is the need to develop students' potential holistically to prepare them to face the demands of future society. The urgency lies in the need for inclusive and diverse education to ensure that every student can develop optimally. This research aims to evaluate the effectiveness of integrating the theory of multiple intelligences in improving student learning in Indonesia. The research method involves direct observation during classroom learning sessions, using the Science Behavior Checklist and Pure Value Observation. Data was collected through structured observation and processed using qualitative analysis methods. The research results show that a learning atmosphere that integrates multiple intelligence elements helps develop students' scientific tendencies and noble values. In conclusion, the integration of multiple intelligence theory in the Indonesian curriculum provides a valuable contribution to developing students' potential holistically, preparing them for academic success, and becoming empowered individuals. The implication of this research is the need to continue to encourage inclusive learning approaches that take into account the diversity of students' intelligence to create a learning environment that supports holistic development.